Application Of Plus Liquid Organic Fertilizer And Leves Truncation Technique On Onion Growth And Yields (JHP17 (Jurnal Hasil Penelitian), 2017)
This study aims to examine the growth and yields of onion resulted by combination of plus organic liquid fertilizer application andleaves truncation technique.Factorial randomized group designwith two factors was used.Factor I istwo levels truncation treatment (P) while factor II is concentration is four levels liquid organic fertilizer (O). Treatment was repeated three times with two (2) samples of plants.  Observationincluded plant length, number of tillers, number and weight of tubers. The average top results in treatment group of liquid organic fertilizer was obtained by concentrations of 6 ml (O3), the length of the plant at the age of 56 DAPwas 60.67 cm, number of leaves at the age of 56 DAPwere 82.50 strands, the number of tubers at the end of the observation was 14.42 and tubers weight at the end observation was 229.08 grams. The lowest result in O0 and truncation treatment provides the highest result compared with plant of non-truncation technique withplant length was 59.83 cm (age of 56 DAP), number of leaves was 83.33 strands (age 56 DAP), the number of tubers was 13.67 (end of observations) and the highest tubers weight was of 229.08 grams (end of observation).